PELAKSANAAN KELAS IBU HAMIL DENGAN MODIFIKASI MENGGUNAKAN PEDOMAN TAHUN 2015 DI WILAYAH KERJA PUSKESMAS TANJUNG KARANG KOTA MATARAM - Khairi, Sabi’ah; Bahtiar, Heri; Aqidah, Fitratul (Stikes Yarsi Mataram, 2021)
Since ten years ego, government has regulated a class program for pregnant women that it helped for encourage mother’s knowledge, attitude and behavior to improving healthy mother and fetus during perinatal period. This community service program aimed to improving knowledge of pregnant women particularly about healthy during pregnancy in work area of Puskesmas Tanjung Karang Mataram (Banjar and Sintung village). This program was conducted with some methods include pre and post test design, health education, interactive dialogue, watching video and pregnant exercise. 20 pregnant women have recruited as participants. The result of this program showed that there was significant increase the knowledge of pregnant women with mean score was 90 point after intervention. Class program of pregnant women should be conducted regularly in the future to improving and maintaining health believe of pregnant women and decrease mother’s mortality rate